Distribution and source of glycerol dialkyl glycerol tetraethers (GDGTs) and the applicability of GDGT-based temperature proxies in surface sediments of Prydz Bay, East Antarctica - Liu, Ruijuan; Han, Zhengbing; Zhao, Jun; Zhang, Haifeng; Li, Dong; Ren, Jianye; Pan, Jianming; Zhang, Haisheng (Polar Research, 2020)
Reliable records of Southern Ocean seawater palaeotemperatures are important because this region plays a significant role in regulating global climate change. Biomarkers such as GDGT-based indices have been effectively used to reconstruct seawater temperatures. We analysed the composition and distribution of iGDGTs, OH-GDGTs and brGDGTs and calculated GDGT-based temperature indices in surface sediments from Prydz Bay, East Antarctica. Our results showed that iGDGTs, OH-GDGTs and brGDGTs are all produced in situ, with iGDGTs and OH-GDGTs mostly synthesized by Thaumarchaeota. Concentrations of iGDGTs, OH-GDGTs and brGDGTs showed similar spatial distributions and decreased from the continental shelf towards the deep ocean. The highest concentrations were in the inner bay, which is attributed to a combination of (1) bathymetry that reduces water exchange, (2) the Prydz Bay Gyre stabilizing the upper water column and (3) sea ice that releases archaea and bacteria. Among the temperature indices based on iGDGTs, OH-GDGTs and combinations therein, those based on OH-GDGTs showed the strongest correlation with seawater temperature. Some OH-GDGT-based indices (e.g., OH-0/OHs, OH-1/OHs, OH-2/OHs and RI-OH′) exhibited a stronger correlation with annual subsurface ocean temperature (100–200 m), which may be related to archaeal habitats and production mechanisms. Our study suggests that RI-OH′ and OH-0/OHs could be used as indicators of annual subsurface ocean temperature in Antarctic marginal seas.
Keywords: Sørishavet; arkebakterier; batymetri; biomarkører; klimaendringer; oseanografi; sjøvann; temperatur; økosystemer

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula - Schram, Julie B; Schoenrock, Kathryn M; McClintock, James B; Amsler, Charles D; Angus, Robert A (Polar Research, 2015)
Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012–May 2013), daily schedule over three months (March–May 2013) and semidiurnal schedule over five weeks (March–April 2013). A notable pH increase (max pH = 8.62) occurred in the late austral spring/summer (November–December 2012), coinciding with sea-ice break-out and subsequent increase in primary productivity. We detected semidiurnal variation in seawater pH with a maximum variation of 0.13 pH units during the day and 0.11 pH units during the night. Daily variation in pH is likely related to biological activity, consistent with previous research. We calculated the variation in dissolved inorganic carbon (DIC) over each seawater measurement frequency, focusing on the primary DIC drivers in the Palmer Station region. From this, we estimated net biological activity and found it accounts for the greatest variations in DIC. Our seasonal data suggest that this coastal region tends to act as a carbon dioxide source during austral winter months and as a strong sink during the summer. These data characterize present-day seawater carbonate chemistry and the extent to which these measures vary over multiple time scales. This information will inform future experiments designed to evaluate the vulnerability of coastal benthic Antarctic marine organisms to ocean acidification. Keywords: Antarctica; aragonite; calcite; pH; seawater chemistry; total alkalinity.
Keywords: Sørishavet; analyser; havis; kjemisk; sjøis; sjøvann

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Culturable heterotrophic bacteria from Potter Cove, Antarctica, and their hydrolytic enzymes production - Tropeano, Mauro; Coria, Silvia; Turjanski, Adrían; Cicero, Daniel; Bercovich, Andrés; Mac Cormack, Walter; Vázquez, Susana (Polar Research, 2012)
Affiliations of the dominant culturable bacteria isolated from Potter Cove, South Shetland Islands, Antarctica, were investigated together with their production of cold-active hydrolytic enzymes. A total of 189 aerobic heterotrophic bacterial isolates were obtained at 4°C and sorted into 63 phylotypes based on their amplified ribosomal DNA restriction analysis profiles. The sequencing of the 16S rRNA genes of representatives from each phylotype showed that the isolates belong to the phyla Proteobacteria (classes Alpha- and Gamma-proteobacteria), Bacteroidetes (class Flavobacteria), Actinobacteria (class Actinobacteria) and Firmicutes (class Bacilli). The predominant culturable group in the site studied belongs to the class Gammaproteobacteria, with 65 isolates affiliated to the genus Pseudoalteromonas and 58 to Psychrobacter. Among the 189 isolates screened, producers of amylases (9.5%), pectinases (22.8%), cellulases (14.8%), CM-cellulases (25.4%), xylanases (20.1%) and proteases (44.4%) were detected. More than 25% of the isolates produced at least one extracellular enzyme, with some of them producing up to six of the tested extracellular enzymatic activities. These results suggest that a high culturable bacterial diversity is present in Potter Cove and that this place represents a promising source of biomolecules. Keywords: Microbial enzymes; Antarctic bacteria; marine bacteria; cold enzymes; psychrophiles.
Keywords: Sørishavet; alger; bakterier; biodiversitet; marin biologi; sjøvann; økologi; økosystemer

The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Excess and deficit of sulfate in polar snow - Gjessing, Yngvar (Atmospheric Environment (1967), 1989)
Keywords: Antarktis; analyser; kjemisk; meteorologi; sjøvann; snø

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Conditional instability of sea water at the freezing point - Foldvik, Arne; Kvinge, Thor (Deep Sea Research and Oceanographic Abstracts, 1974)
Keywords: AABW; Sørishavet; bunnvannet; havis; oseanografi; sjøis; sjøvann